The Problem of Bullying in the Education Sphere: A Case Study of Students with Disabilities - Frontina, Teza; Budiarti, Rosana Rida; Adrian, Daniel Paskah Adi (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Bullying is an act of hurting another person, either physically or verbally. Cases of bullying often occur in the scope of education, one of which is the case of bullying of students with disabilities in Cirebon. This study aims to determine the causes, impacts, and ways that can be done to prevent bullying from the perspective of education in general and Christian religious education in particular. With a literal qualitative approach, data were collected through non-participant observation and secondary documentation studies found in various mass media. As a result, it is known that several external and internal factors cause bullying among students. Examples of the effects of bullying on victims include loss of focus, trauma, and difficulty socializing. Meanwhile, the perpetrators tend to be more violent. Nevertheless, preventive measures such as seminars, social control, parenting improvements, social interaction, and several other precautions can be taken to prevent bullying from occurring among adolescents. Educational psychology in the teaching of Christianity thus becomes an urgent matter to think about together.